2019
DOI: 10.4271/2019-01-2599
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Multiple Piston Motion Control Approaches in a Free Piston Engine Generator

Abstract: <div class="section abstract"><div class="htmlview paragraph">The control and design optimization of a Free Piston Engine Generator (FPEG) has been found to be difficult as each independent variable changes the piston dynamics with respect to time. These dynamics, in turn, alter the generator and engine response to other governing variables. As a result, the FPEG system requires an energy balance control algorithm such that the cumulative energy delivered by the engine is equal to the cumulative en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The Clark group of West Virginia University investigated the operation characteristics and the piston and engine performance of a single-cylinder-type FPELG and a dualcylinder-type FPELG coupled with a mechanical spring on the basis of simulation results and experimental results [8][9][10]. It was found that the operation frequency of the piston and the power of the free piston engine are positively correlated with the spring stiffness, while the efficiency decreased with the increase in spring stiffness [11].…”
Section: Single-cylinder/single-piston Fpelg Structure Type Coupled W...mentioning
confidence: 99%
See 1 more Smart Citation
“…The Clark group of West Virginia University investigated the operation characteristics and the piston and engine performance of a single-cylinder-type FPELG and a dualcylinder-type FPELG coupled with a mechanical spring on the basis of simulation results and experimental results [8][9][10]. It was found that the operation frequency of the piston and the power of the free piston engine are positively correlated with the spring stiffness, while the efficiency decreased with the increase in spring stiffness [11].…”
Section: Single-cylinder/single-piston Fpelg Structure Type Coupled W...mentioning
confidence: 99%
“…Moreover, the combustion characteristics of the FPELG coupling with the mechanical spring were also simulated, and the results demonstrated that the combustion starting timing advanced, the adverse work and heat transfer both increased, while the overall efficiency declined [15]. Yingcong Zhou from Stony Brook University researched The Clark group of West Virginia University investigated the operation characteristics and the piston and engine performance of a single-cylinder-type FPELG and a dual-cylindertype FPELG coupled with a mechanical spring on the basis of simulation results and experimental results [8][9][10]. It was found that the operation frequency of the piston and the power of the free piston engine are positively correlated with the spring stiffness, while the efficiency decreased with the increase in spring stiffness [11].…”
Section: Single-cylinder/single-piston Fpelg Structure Type Coupled W...mentioning
confidence: 99%
“…Mahrous et al [41] studied the effects of the valve overlap (VO) angle on engine performances on the same engine type. They arrived to fix the IV closure and EV opening times and modify the IV opening and EV closing times [45]. The VO angle was reported to influence the airfuel mixture significantly, and the perfect air-fuel mixture was obtained at high VO angles.…”
Section: Introductionmentioning
confidence: 99%